Political uncertainty and investment: Causal evidence from U.S. gubernatorial elections - Jens, Candace E. (Journal of Financial Economics, 2017)
I examine the link between political uncertainty and firm investment using U.S. gubernatorial elections as a source of plausibly exogenous variation in uncertainty. Investment declines 5% before all elections and up to 15% for subsamples of firms particularly susceptible to political uncertainty. I use term limits as an instrumental variable (IV) for election closeness. Because close elections are related to economic downturns, I find that the effect of close elections on investment is understated by more than half by ordinary least squares (OLS). Post-election rebounds in investment depend on whether an incumbent is re-elected. Finally, I provide evidence that firms delay equity and debt issuances tied to investments before elections.